Prevention of Violence Against Women with Adolescents: A Scoping Review (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Violence against women is a serious public health problem in Brazil, especially during adolescence. This study sought, through a scoping review, to synthesize and analyze interventions with adolescents aimed at preventing violence against women. The search for articles was carried out on the Scielo, BVS Bireme and Scopus platforms, with the following inclusion criteria: peer-reviewed articles, written in English, Spanish or Portuguese, published between 2011-2021, which described interventions with adolescents to prevent violence against women, as well as their results. After applying the selection criteria, 16 articles were selected. It should be noted that most of the interventions carried out had few behavioral components and their results indicate changes predominantly focused on attitudes and opinions. It is concluded that these are guidelines focused on behavior change and that behavior analysis has great potential to contribute to this process.
Keywords: Violence against women; Prevention of violence; Scoping review; Behavior skills training; Behavior Analysis